Boats, borders, and bases race, the cold war, and the rise of migration detention in the United States - Loyd, Jenna M., 1973- (University of California Press, 2018)
"Discussions on U.S. border enforcement have traditionally focused on the highly charged U.S.-Mexico boundary, inadvertently obscuring U.S.-Caribbean relations and the concerning asylum and detention policies unfolding there. Boats, Borders, and Bases offers the missing, racialized histories of the U.S. detention system and its relationship to the interception and detention of Haitian and Cuban migrants. It argues that the U.S. response to Cold War Caribbean migrations actually established the legal and institutional basis for contemporary migration and detention, and border-deterrent practices in the United States. This book promises to make a significant contribution to a truer understanding of the history and geography of the U.S. detention system overall."--Provided by publisher.